PANDANGAN ABDULLAH SAEED PADA KONSEP NASKH MANSUKH (ANALISIS SURAH AN-NUR AYAT 2) - Muhammad Nasrullah (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2020)
The theory of naskh mansukh is still a debate between scholars regarding agreement and rejection. And among scholars who agree on the concept of nasikh mansukh in the Qur’an, each has their own criteria in determining the concept of nasikh. One of the scholars who agrees is Abdullah Saeed, a contemporary commentator who offers a new method of interpreting the Qur’an, namely the contextualist method. In this paper, researchers are interested in studying the concept of nasikh mansukh according to Saeed through the problems that occur in naskh mansukh Surah An-Nur verse 2. According to Abdullah Saeed, the concept of naskh mansukh gives a very logical idea that the applicable law may experience cancellation for the sake of fulfill the needs of the people due to different conditions and situations, if in the past the Qur'an was still decreasing then the solution from Allah to meet the needs of the people was to cancel the existing law by lowering new laws or nasikh mansukh, but now that the verses of the Qur’an have been coming down, it is to fulfill the needs ummah is by reciting the Qur’an. And Abdullah Saeed made naskh mansukh as a first step to contextualize the law of the Qur’an.